Inside the goldfish bowl: Bridget O’Connor’s material world. En la pecera: el mundo material de Bridget O’Connor - Sell, Jonathan (Estudios Ingleses de la Universidad Complutense, 2003)
Bridget O’Connor’s two collections of short stories, Here Comes John (1993) and Tell Her You Love Her (1997), anatomist the materialist inhabitants of English consumer society in the 1 980s and 1 990s. The result is a critique of that society and its values, which are reflected in O’Connor’s synoptic and reifying prose style, the use of allusion and the presiding image of the goldfish. The problem is that the short stories’ stylistic affinity with the very society and values they seek to decry may ultimately reduce them to the very status of material and perishable productions which, as works of literature, they may prefer to transcend.
Keywords: Bridget O'Connor; Material world; Consumer society; Synoptic; Allusion